2021
DOI: 10.3390/cancers13040641
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Lymphoma Microenvironment: An Intricate Network Ready for Therapeutic Intervention

Abstract: Follicular Lymphoma (FL), the most common indolent non-Hodgkin’s B cell lymphoma, is a paradigm of the immune microenvironment’s contribution to disease onset, progression, and heterogeneity. Over the last few years, state-of-the-art technologies, including whole-exome sequencing, single-cell RNA sequencing, and mass cytometry, have precisely dissected the specific cellular phenotypes present in the FL microenvironment network and their role in the disease. In this already complex picture, the presence of recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 148 publications
0
7
0
Order By: Relevance
“…Alterations in T-cell phenotype and function have been broadly observed ( 17 20 ). In the FL TME, malignant B cells depend on direct contact with T follicular helper (Tfh) cells, which are essential for the formation and maintenance of the germinal center reaction ( 21 , 22 ). In CLL and DLBCL, investigators have observed altered CD4 + to CD8 + T cell ratio, inverted T helper (Th)1 to Th2 ratio and increased exhausted T cells expressing TIM-3, LAG-3 and PD-1 ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in T-cell phenotype and function have been broadly observed ( 17 20 ). In the FL TME, malignant B cells depend on direct contact with T follicular helper (Tfh) cells, which are essential for the formation and maintenance of the germinal center reaction ( 21 , 22 ). In CLL and DLBCL, investigators have observed altered CD4 + to CD8 + T cell ratio, inverted T helper (Th)1 to Th2 ratio and increased exhausted T cells expressing TIM-3, LAG-3 and PD-1 ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…FL exhibits a high dependence on the tumor microenvironment (TME) composed of different types of immune cells and stromal cells. In lymph nodes, the FL microenvironment mainly consists of CD4+ T follicular helper (Tfh) cells, CD4+ T regulatory cells (Tregs), CD8+ cytotoxic T cells (CTLs), macrophages, follicular dendritic cells (FDCs) and fibroblastic reticular cells (FRCs) [8,9]. Through various soluble factors and ligand-receptor interactions, FL-TME Ivyspring International Publisher crosstalk supports tumor cell survival and proliferation, promotes immune escape, and also serves as promising prognostic biomarker and therapeutic target [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well documented that genetic changes are involved in FL initiation and progression, the interaction between the immune microenvironment and FL tumor cells is acquiring increasing importance [ 10 , 11 , 12 ]. In FL patients, neoplastic follicles maintain an architecture similar to the normal lymph nodes in which B cells remain dependent on cellular and molecular events that contribute to the normal GC and include stromal cells, T-follicular helper cells (Tfh), T-follicular regulatory cells (TFRs), and follicular dendritic cells (FDCs), normally found in the lymphoid follicles [ 13 ].…”
Section: Introductionmentioning
confidence: 99%